Upgrading Traffic Circles to Modern Roundabouts to Improve Safety and Efficiency – Case Studies from Italy - Pratelli, Antonio; Sechi, Paolo; Souleyrette, Reginald Roy (Promet - Traffic&Transportation, 2018)
This paper presents a procedure for analysing safety and operational improvements made possible by converting traffic circles to modern roundabouts. An Italian case study is presented for alternative layouts under various traffic demand scenarios. In the application of the procedure, the average waiting times and queue lengths at entries are computed with an analytical capacity model, using default values for gap parameters. Then, the roundabout is dynamically simulated. The simulation results in a revised set of gap parameters that are in turn used as inputs to a second trial of the capacity model, and in turn fed back into the simulation. The two steps are repeated until the parameters reach a pre-selected convergence criterion, so that gap parameter values for both the static capacity and dynamic microsimulation models are in equilibrium. Therefore, the applied procedure can conduct both static and dynamic roundabout design, usually applied separately. One can start with default values in guidelines and couple them with limited field data, improving both the expected results and cost-effectiveness of solutions. Next, safety is estimated using dynamic simulation software and a compatible conflict counting model to acquire surrogate measures of safety. Level-of-service and surrogate safety indicators for the existing and redesigned roundabouts are then compared. The procedure is first demonstrated on an old “ultra-large” roundabout. The procedure is tested on this roundabout using the Highway Capacity Manual 2016 (HCM2016), AimsunTM, and Surrogate Safety Assessment Model (SSAM) software. A redesign is shown to be far superior in efficiency and safety. Finally, two cases are described where large first generation roundabouts were upgraded to modern standards.